Eid homecoming "Mudik" tradition as a conventional pattern in the global era - IEKE SARTIKA IRIANY; ROSTIENA PASCIANA; ABDULLAH RAMDHANI; MULYANINGSIH (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aims to provide a detailed account of Muslim behavior according to Mudik norms. This is done to learn more about Mudik, the local wisdom that plays an important role in maintaining social harmony, by extracting precise data from its natural habitat.Method: This study used a descriptive qualitative approach through interviews, observations, and written records. Purposive sampling was used in this study, and 27 participants from the Garut Bus Terminal and Garut Train Station were selected randomly as interviewees. Reduction, presentation, analysis, and interpretation were all used to parse and draw conclusions from the data.Findings: The findings demonstrate that Mudik, as indigenous knowledge, is still practiced for the same reason it was originally developed: to promote social cohesion and unity in the modern, interconnected world. According to in-depth interviews, most participants enjoyed the well-planned celebration of Eid. It turns out that the only place in the world where Muslims "over" celebrate Eid al-Fitr is Indonesia, where the holiday is associated with the end of a month-long fasting period that begins on the first day of the Islamic lunar calendar month of Shawwal.Implications/Novel Contribution: Insights into the complexities of the Mudik phenomenon can be gained from various disciplines, including sociology, religion, and economics, making this discussion all the more vital. In light of these findings, the recommendations made for future research into the positive economic effects of Eid homecoming are intriguing.